PERSPEKTIF ETIKA PROFESI DAN ETIKA BISNIS: STUDI KASUS PT ASABRI - Baity, Namira Nur; Bastiansyah, Dodi; Argunanto, Argunanto; Nofryanti, Nofryanti (LPPM Universitas Bina Bangsa, 2025)
This study aims to investigate PT ASABRI (Persero) in terms of violations of professional ethics and business ethics related to fraud in the process of preparing financial statements. A qualitative approach with literature review is the method used, by collecting primary and secondary data. To evaluate the fraud that occurred in a state-owned enterprise that manages social insurance programs for members of the military and police, the data collected was analysed using professional and business ethics standards. PT ASABRI was established to manage social insurance for members of the military, police, and certain government employees. This institution originated from the establishment of Taspenmil in 1964. Fraud in this context impacts business ethics, damages the business environment, reduces the trust of the government, investors, and the public, and harms the state due to manipulated financial statements. The breach of professional ethics in this case is contrary to the principles of the professional body (IAPI), including integrity, objectivity, and professionalism